2014
DOI: 10.1302/0301-620x.96b11.33963
|View full text |Cite
|
Sign up to set email alerts
|

Clinical negligence in foot and ankle surgery

Abstract: We present a review of litigation claims relating to foot and ankle surgery in the NHS in England during the 17-year period between 1995 and 2012. A freedom of information request was made to obtain data from the NHS litigation authority (NHSLA) relating to orthopaedic claims, and the foot and ankle claims were reviewed. During this period of time, a total of 10 273 orthopaedic claims were made, of which 1294 (12.6%) were related to the foot and ankle. 1036 were closed, which comprised of 1104 specific complai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“… 10 Interestingly, in this study, death did not increase the chance of successful litigation, again supporting the notion that routinely discussed postoperative complications are less likely to result in indemnity payments, even with the ultimate outcome of death. 23 …”
Section: Discussionmentioning
confidence: 99%
“… 10 Interestingly, in this study, death did not increase the chance of successful litigation, again supporting the notion that routinely discussed postoperative complications are less likely to result in indemnity payments, even with the ultimate outcome of death. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The 13 articles reviewed were published between 2003 and 2019. Collectively, the 13 studies [1,[5][6][7][8][9][10][11][12][13][14][15][16] analyzed data on 23,716 claims related to orthopedic surgery from a private collection, single-center institutions, and various databases, including the Physician Insurers Association of America, VerdictSearch, and National Health Service Litigation Authority in the United Kingdom. The date ranges of claims reviewed went as far back as 1985 from the Physician Insurers Association of America to cases in 2016 from the Westlaw database.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, it was found that lawsuits related to lower extremity injury were more common than those of upper extremity injury, which was more common than axial skeleton. The other 4 studies were specific to a body part (scaphoid, ankle, shoulder, and elbow) [5,12,13,15] . The upper limb was most commonly involved in the 2 pediatric studies included in the review [7,9] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations